Standards probatórios e epistemologia jurídica: uma proposta interdisciplinar para a valoração do testemunho no processo penal - Fernandes, Lara Teles (2019)
This paper aims to approach the need to modify the way of reasoning with eyewitness evidence and identification procedures in the system of criminal justice in Brazil, in order to change the perspective based on cognitive neutrality and presumptions of accuracy, in which the eyewitness is considered the inescapable messenger of the truth in criminal proceedings. The reason for this research is the relevance of this kind of evidence in the criminal practice of the country - since, according to a survey guided by Department of Justice and IPEA, the eyewitness evidence joins 90% of the criminal cases, while an identification procedure is mentioned as sufficient to convict somebody in 77% of the cases - as well as its potential to produce false convictions, according to the Innocence Project, which has listed the misidentification as the most frequent cause of exonerations (72%). So, the research was divided into three chapters. The first part focuses on raising the epistemological premises for the construction of an adequate proposal for reasoning with testimonies, as well as the study of the relation between evidence and truth and the atomistic, holistic and hybrid theories of reasoning with proof. In turn, the second section intends to analyze the peculiarities of the justification of truth in the criminal process, in which the dogma of real truth is approached, with the use of epistemology as the subject of its overcoming, due to its obsolescence, since related to judicial practices endowed with epistemological emptiness, that ignore the cognitive limitations of procedural subjects. In addition, another important concept is also presented: the standard of proof. Finally, in the third chapter, the current state of identification and testimonies practices in Brazil is highlighted. Then, inspired by the knowledge from Cognitive Psychology and Neurolaw to unveil the cognitive limitations of the witnesses – branched out in perceptual, recovery and language failures – and the cognitive biases of the judges, a proposal is presented, founded in the hybrid theory of reasoning with evidence, in order to accomplish the standard of proof with fairness and to prevent false convictions. This is as an alternative until reaching the ideal independence of the criminal justice system on this evidence. The conclusion is that these parameters should be 1) the credibility of the eyewitness, 2) the reliability of the version, 3) the analysis of false memories, 4) the way of collecting the testimonies, 5) the identification procedure and the factors that minimize its accuracy, 6) the inefficiency of double identifications, (7) the exceptionality of the hearsay statement, and 8) the existence of a dialectical inquiry. The methodology used is of an eminently qualitative nature, and the work is carried out through indirect research, through a bibliographic research, with an exploratory, descriptive, and propositive approach.